Case Report of a 17 Year Young Adult with Dermmoid Cyst in Thymus (University Heart Journal, 2015)
Teratoma of thymus gland is a rare variety of anterior mediastinaltumour. It may cause compression over airway resulting respiratory depression. This is a case of a 17 yearyoung adult, farmer, presented with swelling over front of root of neck for 1 month with history of surgery over the same region 4 months back. Clinically two oval, pedunculated masses were found. CT scan of chest revealed enlargement of thymus. FNAC of the mass could not exclude possibility of mesenchymal or thymic neoplasm. Peroperativelythymus was found enlarged and was variegated in appearance (dermoid and gelatinous material was found). Thymus was resected in toto. Excision of sinus tract was also done. His operation was uneventful, postoperative recovery was excellent. He was discharged to home on 14th postoperative day with good physical condition. Although rare, mediastinalteratoma should be considered as a differential diagnosis of anterior mediastinaltumours. Early diagnosis and complete excision is necessary. Possibility of malignant change should also be considered.University Heart Journal Vol. 10, No. 1, January 2014; 47-50